«Textes flottants»: l’exemple d’Abū Šāma. Une écriture de l’histoire dans le Proche-Orient aux VIIe–IXe/XIIIe–XVe siècles - Roiland, Muriel (Der Islam, 2017)
Abū Šāma lived as an historian and a biographer in 7th/13th-century Damascus. Although he took care to transmit a fair copy (mubayyaḍa) of his Kitāb al-Rawḍatayn and the two other chronicles he wrote, drafts of his texts, containing additions and variants he did not authenticate, circulated and were later edited. We refer to these copies and editions as “floating texts”. Furthermore, we managed to reconnect two manuscript copies, kept in the British Library, which were made from the autograph of theKitāb al-Rawḍatayn. Ibn Ṣaṣarā, a famous Damascene qāḍī, copied the text together with Abū Šāma’s certificates of transmission (iǧāza). Afterwards, several scribes accurately transcribed these certificates as if they were part of the text. We therefore label them “fossils”.